The human adult skull with complete metopic suture - a case report - Grzegorz Wróbel (Kazimierz Wielki University, 2017)
In the recent years, variations of cranial sutures are commonly studied because of their significance in various fields of medicine and surgery. The metopic suture is a dentate-type suture extending from the nasion to the bregma. The incidence of the metopism and difference in shapes varies by races. The fact is that metopism appears more frequently among women than men. The aim of this work is to analyze case to the human skull of an adult (female), originating from excavations in the vicinity of Kielce. The skull comes from the osteological collection of the Department of Anatomy, Faculty of Medicine and Health Sciences, Jan Kochanowski University. The knowledge of the anatomy of the metopic suture is important because its permanence can be mistaken for a cranial fracture in radiological images, or even for the sagittal suture. It is also important for anthropology and forensic medicine.